The Legacy of A Common Faith in the Thought of Philip H. Phenix - Scribner, Campbell (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
The following article traces the legacy of John Dewey’s A Common Faith (1934) and Dewey’s concept of “the religious” in the thought of Philip H. Phenix, a prominent philosopher of education during the 1950s and 1960s. Phenix frequently cited A Common Faith and echoed Dewey’s commitments to naturalism, creativity, and ethical commitment, all of which he associated with transcendent sources of meaning. In this respect, Phenix’s position was almost identical to Victor Kestenbaum’s subsequent interpretation of Dewey in The Grace and the Severity of the Ideal (2002). Unlike Kestenbaum, however, Phenix found no trace of transcendence in A Common Faith and repeatedly criticized Dewey on the point. This article ascribes Phenix’s attachment to the transcendent and his interpretation of A Common Faith to contemporary changes in science and religion, particularly the intellectual influence of theoretical physics and existentialist theology, with implications for our understanding of religious and educational thought at midcentury.